Killing Reagan : the violent assault that changed a presidency - O'Reilly, Bill; Dugard, Martin (Henry Holt and Company, 2015)
"Just two months into his presidency, Ronald Reagan lay near death after a gunman's bullet came within inches of his heart. His recovery was nothing short of remarkable -- or so it seemed. But Reagan was grievously injured, forcing him to encounter a challenge that few men ever face. Could he silently overcome his traumatic experience while at the same time carrying out the duties of the most powerful man in the world?,"--Novelist.